Barriers of value management implementation for building projects in Egyptian construction industry - Othman, I. (Ain Shams University, 2021)
This research aims to address barriers and obstacles to the adoption of value management (VM) in the Egyptian building projects. Furthermore, the primary contribution of this research paper is to establish the current level of the VM implementation in the Egyptian construction industry which is the first research that appears this level. The research was limited to the regions of Cairo and Giza, and clients, consultants, and contractors with sufficient experience in building construction management are the key participants. With a view to find answers from those who work actively as part of the construction industry, a quantitative questionnaire survey was used. The analysis of the collected data was based on descriptive statistical tools. Research shows that the critical barriers in the construction industry are inadequate facilitation of skills and training, and difficulty in the involvement of decision-makers and other key partners in the VM workshop. The results constitute barriers to VM implementation in the country and its guidelines will significantly promote VM adoption, both in the country and in other developing nations, where the same projects are carried out. On the other hand, this study concluded that implementation and usage of the VM technology concept within the organization has a significant impact on professionals and management skills. Â© 2020